Perceived stigma in Korean adolescents with epilepsy: Effects of knowledge about epilepsy and maternal perception of stigma. (January 2015) - Ryu, Han Uk; Lee, Sang-Ahm; Eom, Soyong; Kim, Heung-Dong
Highlights: We determined the impact of knowledge about epilepsy on AWE's perceived stigma. Korean AWE and their mothers had a much low level of knowledge about epilepsy. AWE's knowledge about epilepsy was related to the AWE's perception of stigma. Polypharmacy and maternal concealment behavior were related to the AWE's stigma. Abstract: Purpose: There has been little research on whether the knowledge that adolescents with epilepsy (AWE) or their family have about the condition reduces their perception of stigma. In this study we determine the relation between AWE's perceived stigma of, and knowledge about, epilepsy and maternal perception of stigma. Methods: This was a cross-sectional multicenter study involving AWE and their mothers from 25 secondary or tertiary hospitals in Korea. The level of knowledge about epilepsy was assessed using 34 medical items of the Epilepsy Knowledge Profile-General (EKP-M). Additional questionnaires included the Child Stigma Scale, Parent Stigma Scale, and the Maternal Disclosure Management Scale. Results: A total of 243 AWE and their mothers were included. The mean EKP-M score was 20.7 (range, 12–31) for AWE and 22.0 (range, 11–31) for their mothers. AWE and mothers had a neutral perception of stigma on average, but the maternal concealment behavior was high. Multiple linear regression indicated that AWE's knowledge about epilepsy was significantly related to their perception of stigma. Unexpectedly, AWE with a low level of knowledge reported a higher perception of stigma than those with a very low level of knowledge ( β = 0.280, p = 0.040). In addition, higher maternal concealment behavior ( β = 0.070, p = 0.002) and receiving polytherapy ( β = 0.240, p = 0.046) were independent factors predicting higher perception of stigma in AWE. Conclusion: The knowledge that the AWE had about their epilepsy, maternal concealment behavior, and receiving polytherapy were significantly related to the AWE's perception of stigma.